Ketengikan Daging Ayam Kampung Unggul Sinjai (AKUSI) Yang Dimarinasi Menggunakan Bubuk Kulit Nanas dan Waktu Marinasi Yang Berbeda - Azmi Mangalisu; Armita Permatasari (Politeknik Negeri Jember, 2020)
Ayam Kampung Unggul Sinjai (AKUSI) is a type of native chicken that is slaugthered when culled,has tough and easily rancid. The marination process using pineapple peel powder is expected toreduce meat rancidity. The purpose of this study was to carry out a marination process usingpineapple peel powder at different times and its effect on meat rancidity. This study used aCompletely Randomized Design (CRD) factorial pattern with 2 factors, namely the marinationprocess using pineapple peel powder and different times. The variables tested in this study werethe pH and TBA value. The data obtained were analyzed by analysis of variance and further testedthe Least Significant Difference (LSD). The results showed that culled AKUSI rancidity could bereduced by marination process using pineapple peel powder. The provision of pineapple peelpowder at 15% with 90 minutes marination time was the best marination to reduce the meatrancidity.